A UNIVERSIDADE EM EXPANSÃO: DA GESTÃO DO ENSINO À FORMAÇÃO DO CORPO TÉCNICO-ADMINISTRATIVO - Cássio Cassel (Universidade Federal de Santa Catarina, 2016)
From the process of expansion of higher education and focus on the promising university market estableshed in Brazil, this study a nalyzed the educational technologies as tools to support the management and development of teams. Therefore, in addition to literature revision related to educational policies and technologies, this case study included participant observation, which made i t possible to deepen the reality of the managers responsible for staff that work in units that are distant from the headquarters. During the study, it was observed that the institution, which uses advanced educational technologies and has been recognized f or excellence in teaching, demonstrates enormous difficulty in the development of their teams, which showed a misalignment, particularly in the area of Human Resources compared to the teaching areas. Faced with this, the study reinforces the need for all a reas of an institution to be aligned with the expansion process, and points to the importance of educational technologies in the training of employees and alignment of teams.